The association between family adaptability and adolescent depression: the chain mediating role of social support and self-efficacy - Lin, Yanyan; Jia, Guangyunxian; Zhao, Zirong; Li, Meng; Cao, Guanghai (Frontiers in Psychology, 2024)
Previous research has shown a correlation between family adaptability and adolescent depression. However, there is a lack of studies that have investigated the underlying mechanism between family adaptability and adolescent depression. Based on the Ecological Systems Theory, this study aims to investigate the link between family adaptability and depression in adolescents, mediated by the sequential roles of social support and self-efficacy. The sample consisted of 1086 students randomly selected from seven public middle schools in Shandong Province, Eastern China. All the participants filled in the structured self-report questionnaires on family adaptability, social support, self-efficacy, and depression. The data were analyzed using SPSS 25.0 and Structural Equation Modeling (SEM) in AMOS 24.0. The findings of this study are as follows: (1) Family adaptability is negatively associated with adolescent depression; (2) Social support plays a mediating role between family adaptability and adolescent depression; (3) Self-efficacy plays a mediating role between family adaptability and adolescent depression; (4) Social support and self-efficacy play a chain mediation role between family adaptability and adolescent depression. It is suggested that early interventions and support should be provided to facilitate adolescents' family adaptability, social support, and self-efficacy, thus reducing their depression and improving mental health of adolescents.